Framework Administered Account for Selected Fund Activities : West Africa Regional Technical Assistance Center (AFRITAC West) Subaccount. (Policy Papers; Policy Paper, 2009)
In March 2009, the Fund established a new Framework Administered Account to administer external financial resources for selected Fund activities (the 'SFA Instrument'). The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of a subaccount within the SFA. The subaccount for the West Africa Regional Technical Assistance Center (AFRITAC West) would be the fourth one under the SFA. This paper requests Executive Board approval to establish the AFRITAC West subaccount under the terms of the SFA Instrument.